Preparation of IgY Oriented Conjugated Fe3O4 MNPs as Immunomagnetic Nanoprobe for Increasing Enrichment Efficiency of Staphylococcus aureus Based on Adjusting the pH of the Solution System - Shi, Xuening; Sun, Hongbin; Li, Hang; Wei, Shengnan; Jin, Jin; Zhao, Chao; Wang, Juan; Li, Hui (Frontiers in Public Health, 2022)
Immunomagnetic separation based on Fe3O4 magnetic nanoparticles (MNPs) had been widely performed in sample pretreatment. The oriented conjugation strategy can achieve better capture effect than the EDC/NHS method. However, IgY cannot be oriented through SPA strategy like IgG. In this paper, an oriented conjugation nanoprobe was prepared for enrichment of bacteria based on pH adjusting. The main factors affecting the enrichment efficiency were studied, including the pH of the buffer system, the concentration of IgY, the concentration of nanoprobe and the enrichment time. Under the optimal conditions, the enrichment efficiency towards target bacteria could reach 92.8%. Combined with PCR, the LOD was found to be 103 CFU/mL, which was lower than the PCR only. In conclusion, we provided a new protocol for the oriented conjugation of IgY and high sensitivity detection with simple pretreatment.